THE MANIFESTATION OF THE MICROPOLITICS IN CURRICULUM DEVELOPMENT - Kairienė, Aida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The purpose of the research paper is to disclose the manifestation of micropolitics in curriculum development. The objectives of the research are: 1) to analyze scientific literature by presenting the main concepts; 2) to discuss how they help to develop a curriculum. The novelty is that the research is based on the postructuralism theory, where micropolitics is not only a resistance, but also a novelty, in this case self-education. The research method is hermeneutic review of literature. It is important to understand the meaning and importance of individual texts, which, in turn, can be seen as parts of the whole body. The analysis of scientific literature revealed that the main concepts are the following: rhizome, assemblages, the strata, and micropolitics. Self-education should be implemented through rhizomatic learning, observation of self-education, creation of new learning territories and a favourable micro environment.